[2,3]-Sigmatropic Rearrangement of Arylhydroxylamines: Rapid Access to ortho-Sulfonylated Anilines - Liu, Yue; Xu, Gaofei; Gao, Hongyin (Synlett, 2022)
In the absence of transition-metal catalysts and additional oxidants, arylhydroxylamines can undergo an unconventional O-sulfinylation/[2,3]-sigmatropic rearrangement/rearomatization cascade with trifluoromethylsulfinyl chloride to rapidly and efficiently synthesize versatile ortho-sulfonylated aromatic amines. This Synpacts article describes the discovery, further study, and practical application of the rearrangement reactions in arylhydroxylamine compounds and highlights our recent advances in this area.1 Introduction2 Discovery of a New Reaction3 O-Sulfinylation of Arylhydroxylamines Followed by [2,3]-σ Rearrangement4 Conclusion
Keywords: arylhydroxylamines; ortho-sulfonylated anilines; sigmatropic rearrangement; trifluoromethanesulfonylation; DFT calculation